Efficacy and safety of a novel cost-effective suspension arthroplasty technique compared to traditional trapeziectomy with abductor pollicis longus arthroplasty Once Looped Around (OLA)/ Once Looped Inside (OLI) in basal thumb arthritis - Giuseppe Parrone; Adriano Cannella; Giulio fioravanti Cinci; Matthew Charles Giordano; Arturo Militerno; Andra De Matthaeis; Ludovico Caruso; Rocco De Vitis (Medicinski glasnik, 2025)
Aim: Trapeziometacarpal (TMC) joint osteoarthritis is a common source of wrist pain, predominantly affecting women aged 45 to 70 years. While traditional surgical options like trapeziectomy with abductor pollicis longus (APL) arthroplasty are effective, their limitations in advanced disease stages have led to the exploration of alternative techniques. This study compares the clinical outcomes of conventional trapeziectomy with APL arthroplasty to a novel personalized suspensory arthroplasty technique. Methods: A retrospective analysis was conducted on 150 patients with Stage III-IV TMC osteoarthritis who underwent either the conventional APL arthroplasty (n=65) or the novel suspensory arthroplasty (n=85) in the period between 2015 and 2018. Outcomes were assessed using the Numeric Pain Rating Scale (NPRS), Disabilities of the Arm, Shoulder, and Hand (DASH) scores, thumb range of motion, grip strength, and patient satisfaction. Statistical analyses included t-test, χ2 test, and repeated measures ANOVA. Results: Both surgical groups demonstrated significant pain reduction and functional improvement postoperatively. The novel technique resulted in lower NPRS and DASH scores, greater thumb metacarpophalangeal joint flexion-extension, and higher patient satisfaction compared to the traditional method. The prevalence of complications, particularly flexor carpi radialis (FCR) tendinitis, was also lower with the novel technique. Radiographic assessments indicated stable joint positions postoperatively in both groups. Conclusion: The novel personalized suspensory arthroplasty technique offers superior clinical outcomes compared to traditional APL arthroplasty, with enhanced pain management, improved function, and reduced complications. This approach represents a cost-effective and minimally invasive alternative for advanced TMC osteoarthritis, leading to better patient satisfaction and faster recovery.
Keywords: arthritis; arthroplasty; thumb